Abundance of zinc in the red giants of Galactic globular cluster 47 Tucanae - Černiauskas, Algimantas; Ludwig, Hans-Günter; Caffau, Elisabetta (Astronomy and astrophysics, 2018)
Aims. We investigate possible relations between the abundances of zinc and the light elements sodium, magnesium, and potassium in the atmospheres of red giant branch (RGB) stars of the Galactic globular cluster 47 Tuc and study connections between the chemical composition and dynamical properties of the cluster RGB stars.Methods. The abundance of zinc was determined in 27 RGB stars of 47 Tuc using 1D local thermal equilibrium (LTE) synthetic line profile fitting to the high-resolution 2dF/HERMES spectra obtained with the Anglo-Australian Telescope (AAT). Synthetic spectra used in the fitting procedure were computed with the SYNTHE code and 1D ATLAS9 stellar model atmospheres.Results. The average 1D LTE zinc-to-iron abundance ratio and its RMS variations due to star-to-star abundance spread determined in the sample of 27 RGB stars is 〈[Zn/Fe]〉1D LTE = 0.11 ± 0.09. We did not detect any statistically significant relations between the abundances of zinc and those of light elements. Neither did we find any significant correlation or anticorrelation between the zinc abundance in individual stars and their projected distance from the cluster center. Finally, no statistically significant relation between the absolute radial velocities of individual stars and the abundance of zinc in their atmospheres was detected. The obtained average [Zn/Fe]1DLTE ratio agrees well with those determined in this cluster in earlier studies and nearly coincides with that of Galactic field stars at this metallicity. All these results suggest that nucleosynthesis of zinc and light elements proceeded in separate, unrelated pathways in 47 Tuc.